Selection Of Internet Provider To Improve Quality Of Service And Learning Using Decision Support System - Yulifda Elin Yuspita; Prasuci Nanda Minova; Ahmad Dori Pelita Ansara (Institute of Computer Science (IOCS), 2022)
During this pandemic, all kinds of activities are carried out online, including Education activities, learning is carried out online both at the elementary school to tertiary level, besides that the Minister of Education and Culture said that the priority for independent learning in 2021 would focus on eight priorities and one of them is digitalization that focuses on media public relations and media models. Digital education in this case the internet is one of the most important things to support these activities, if there is a disruption to the internet it will affect the learning process and academic services in an institution. Based on this policy, a decision-making policy is needed in determining the appropriate internet provider according to needs. The strong reason to look for in this research is the number of internet providers that offer fast, stable internet services and affordable prices, but in reality the network provided is not able to facilitate internet needs. A decision support system that is flexible and can provide answers quickly can help top management in making decisions. The results of the decision support system research using the Topsis algorithm method which is to provide ranking of the best alternatives and solutions. A decision support system that is flexible and can provide answers quickly can help top management in making decisions. The results of the decision support system research using the Topsis algorithm method which is to provide ranking of the best alternatives and solutions. A decision support system that is flexible and can provide answers quickly can help top management in making decisions. The results of the decision support system research using the Topsis algorithm method which is to provide ranking of the best alternatives and solutions.